Elements of the social system - Sukadi, Imam; Chauhan, Rahul; Artha, Ruly; Rajpurohit, Neel; Ibrahim, Mohd. Hairy (Linguistics and Culture Review, 2021)
In a social system it is not the nature of the means that matters. The focus of sociologists’ attention lies in the problem of use as a process that is closely related to social systems. For example, in today’s world there are people who do not want to eat pork, beef or horse, but for the cow, or horse, they are only a means, namely food for many people. This happens because of differences in value. In a social system there will be elements of pressure and tension. This arises because not even two people have exactly the same interpretation of the role and position of status, in any social system. The social system will experience pressure if there are differences in interpretation and when those differences turn into patterns of action. Tension is a form of behavior that cannot be separated from pressure because pressure is the source of restraint. This tension is closely related to the level of restraint received by a person from an individual or group. This restraint is intended by the pressure to avoid the tendency to deviate from the norm. Of course, those who are oppressed or restrained face it with tension.